First experience with 224Radium-labeled microparticles (Radspherin®) after CRS-HIPEC for peritoneal metastasis in colorectal cancer (a phase 1 study) - Larsen, Stein Gunnar; Graf, Wilhelm; Mariathasan, Anthony Burton; Sørensen, Olaf; Spasojevic, Milan; Goscinski, Mariusz Adam; Selboe, Silje; Lundstrøm, Nadja; Holtermann, Anne; Revheim, Mona-Elisabeth; Bruland, Øyvind Sverre (Frontiers in Medicine, 2023)
Background: Peritoneal metastasis (PM) from colorectal cancer carries a dismal prognosis despite extensive cytoreductive surgery and hyperthermic intraperitoneal chemotherapy (CRS-HIPEC). With a median time to recurrence of 11-12 months, there is a need for novel therapies. Radspherin® consists of the α-emitting radionuclide radium-224 (224Ra), half-life 3.6 days, adsorbed to a suspension of biodegradable calcium carbonate microparticles designed to give short-range radiation to the serosal peritoneal surface linings killing free-floating and/or tumor cell clusters remaining after CRS-HIPEC. Methods: A first-in-human phase-1 study (EudraCT 2018-002803-33) was conducted at two specialized CRS-HIPEC centers. Radspherin® was administered intraperitonellay 2 days after CRS-HIPEC. Dose escalation at increasing activity dose levels of 1-2-4-7-MBq, a split-dose repeated injection and expansion cohorts evaluated the safety and tolerability of Radspherin®. The aim was to explore maximal tolerated dose and biodistribution using gamma-camera imaging. Results from the planned safety interim analysis after completion of the dose-limiting toxicity (DLT) period of 30 days are presented. Results: Twenty-three patients were enrolled; 14 in dose escalation cohort, three in repeated cohort and six in the expansion cohort. Seven males and sixteen females; median age 64 years (28-78). Twelve had synchronous PM Stage IV and 11 metachronous PM (primary Stage II (6), Stage III (5)), disease-free interval 15 months (3-30). Peritoneal cancer index was median 7(3-19), operation time 395 minutes (194-515) and hospital stay 12 days (7-37). Sixty-eight Grade 2 adverse events were reported for 17 patients during the first 30 days, most were low grade and considered related to CRS and/or HIPEC. Only 6 of the TEAEs were evaluated as related to Radspherin®. One TEAE was reported, anastomotic leakage, was reported as grade 3. Accordion ≥3 grade events occurred in a total of 4 of the 23 patients; reoperation due to anastomotic leaks (2) and drained abscesses (2). No dose-limiting toxicity (DLT) was documented at the 7MBq dose level that was then defined as the recommended dose. The biodistribution of Radspherin® showed a relatively even peritoneal distribution. Conclusions: All dose levels of Radspherin® were well tolerated with DLT not reached. No deaths occurred and no serious adverse events were considered related to Radspherin®.